Catching up after COVID-19: do school programs for remediating pandemic-related learning loss work? - de Bruijn, Anne G. M.; Meeter, Martijn (Frontiers in Education, 2023)
Introduction: COVID-19 had a major impact on education, resulting in learning losses among students. The Dutch ministry set-up a subsidy for schools to implement catch-up programs in tackling learning losses. In this study, we examine a) which students participated in the programs, and b) effectiveness of these programs in remediating learning losses in secondary school students. Methods: Sixteen program in eight secondary schools were analyzed using data of 16,675 students (9784 individual students; 1336 participating in a catch-up program). Schools implemented three program types: tutoring, homework support, and general skills. Per school, a difference-in-difference design was used, computing two effect sizes: comparing grades of participating and non-participating students; and grades in tutoring-specific subjects to non-tutored subject (specifically for tutoring programs). Effect sizes were combined using meta-analytic regressions in JASP. Results: At program onset, students selected for participation had significantly lower overall grades than non-participants, orfor subject-specific tutoringlower grades specifically in the tutored subject. Tutoring programs significantly increased students' grades: with higher grades for participants than non-participants, andfor students receiving subject-specific tutoring -higher grades in tutored subjects compared to those in non-tutored subjects. No significant effects were found for homework support and general study skill programs. Conclusion: Schools selected students most in need for catch-up programs. Tutoring interventions seemed to remediate part of secondary school students' learning losses, whereas general skills programs and homework support programs did not. Large between-school heterogeneity was found, implying that program implementation was at least as important as program type and content.